Cybersecurity Infrastructure Compliance Key Factors to Detect and Mitigate Malware Attacks in SMEs: A Systematic Literature Review - Adnan Bin Amanat Ali; Ramesh Kumar Ayyasamy; Rehan Akbar; Abdulkarim Kanaan Jebna; Kiran Adnan (SAGE Open)
Malwares are growing exponentially and are becoming challenging with time, especially for Small and Medium Enterprises (SMEs). As the backbone of a nation’s economy, SMEs face challenges due to limited knowledge, awareness, and resource constraints. These hurdles hinder their adoption of existing frameworks and policies. Existing studies do not explore vulnerabilities within SMEs regarding their effective compliance with the cybersecurity infrastructure to mitigate malware attacks. This research is conducted through a Systematic Literature Review (SLR) using the PRISMA framework. Through this systematic inquiry, we have successfully identified the vulnerabilities and mitigation factors to deal with malware attacks. This SLR uncovers the vulnerabilities, emphasizing non-compliance with cybersecurity infrastructure. To confront these vulnerabilities, a mapping framework using concept maps is proposed. The study contributes to enhancing SMEs’ awareness about the consequences of non-compliance with cybersecurity infrastructure and equipping them with effective measures for vulnerability management.